Health behaviours of young adults during the outbreak of the Covid-19 pandemic - a longitudinal study - Ewelina Czenczek- Lewandowska; Justyna Wyszyńska; Justyna Leszczak; Joanna Baran; Aneta Weres; Artur Mazur; Bogumił Lewandowski (BMC, 2021)
Abstract Background The outbreak of the Covid-19 pandemic has created a number of obstacles to daily functioning, which have led to a need for major changes in lifestyles. The aim of the study was to assess whether and to what extent the outbreak of the Covid-19 pandemic has affected the health behaviours of young adults. Methods 506 people aged 18 to 34 ( x ¯ $$ \overline{x} $$ =24.67 years ±4.23 years) who filled in an online survey were qualified for the study. Assessment was made of eating habits (a modified Food Frequency Questionnaire, FFQ), physical activity and sedentary behaviours (International Physical Activity Questionnaire, short form IPAQ-SF), sleep quality (The Pittsburgh Sleep Quality Index, PSQI), and generalized anxiety (Generalized anxiety Disorder, 7-item, GAD-7 scale). Results During the pandemic, young adults changed their dietary preferences toward sweets and cereal products, increased alcohol (p < 0.001) and fat (p = 0.005) intake, significantly reduced their physical activity (from 8752.5 metabolic equivalents (MET) min/week vs. 6174.6 MET min/week, p < 0.001), increased the time spent sedentarily (Me = 240 min vs. Me = 360 min, p < 0.001) and had decreased sleep quality (PSQI score Me = 7.00 vs. Me = 9.00). Conclusions The Covid-19 pandemic worsened health behaviours and intensified the feeling of generalized anxiety in young adults. Generalized anxiety during obligatory lockdown had the greatest negative impact on sedentary behaviours and sleep quality.